Cell-free supernatant of Levilactobacillus brevis (RAMULAB51) from coconut inflorescence sap (Neera) enhances glucose uptake and PPAR-γ in 3T3-L1 adipocytes and inhibits α-glucosidase and α-amylase - Kumari V B, Chandana; Ramu, Ramith; Shirahatti, Prithvi S.; Alam, Perwez; Wong, Ling Shing (Frontiers in Microbiology, 2024)
IntroductionLactic acid bacteria are prized for their probiotic benefits and gut health improvements. This study assessed five LAB isolates from Neera, with RAMULAB51 (Levilactobacillus brevis, GenBank ON171686.1) standing out for its high hydrophobicity, auto-aggregation, antimicrobial activity, and enzyme inhibition. It evaluated RAMULAB51’s potential in probiotics and diabetes management, focusing on its effects on digestive enzyme inhibition, glucose uptake, and adipocyte function.MethodsIsolates were characterized by Gram staining, catalase reaction, growth at 37°C, and tolerance to phenol, pH, and gastrointestinal conditions. Molecular identification using 16S rRNA sequencing. Evaluations included hydrophobicity, auto-aggregation, HT-29 cell line adhesion, antimicrobial activity, and antibiotic susceptibility. Enzyme inhibition was measured for α-glucosidase and α-amylase using cell-free supernatant, cell extract, and intact cells. Adipogenesis was assessed through Oil-Red O staining, gene expression analysis (PPAR-γ, C/EBPα, Adiponectin, Glut-4, FAS), and glucose uptake assays on 3T3-L1 cells.ResultsAll isolates showed good tolerance to pH (≤9.15 CFU/ml), phenol (≤9.90 CFU/ml), hydrophobicity (≤78.14%), and auto-aggregation (≤92.23%). RAMULAB51 demonstrated the highest tolerance, hydrophobicity, and auto-aggregation. It strongly co-aggregated with Micrococcus luteus and Bacillus subtilis, showing significant antimicrobial activity with a 24 mm inhibition zone against Micrococcus luteus. All isolates were sensitive to Ampicillin, Azithromycin, Streptomycin, and Tetracycline, but resistant to Methicillin and Vancomycin. RAMULAB51 demonstrated the highest enzyme inhibition: α-glucosidase (68.45% CFS, 60.18% CE, 42.15% IC) and α-amylase (80.74% CFS, 61.23% CE, 35.12% IC). By inhibiting these digestive enzymes, RAMULAB51 reduces the conversion of carbohydrates into glucose, thereby decreasing blood glucose levels. This reduction in circulating glucose subsequently influences adipocyte function, as evidenced by the enhanced glucose uptake (1000 µg/mL) and upregulation of PPAR-γ, C/EBPα, Adiponectin, and Glut-4, alongside the downregulation of FAS.ConclusionThe study highlights RAMULAB51’s potential for improving glucose and lipid metabolism. Further, in vivo research is needed to explore its full therapeutic benefits. These findings confirm RAMULAB51’s significant probiotic potential and its promise for diabetes management, warranting further clinical investigation.